Human-behavioural micro-foundations of dynamic capabilities: a systematic review of the last two decades of research - Gheitarani, Fatemeh (2022)
Given the importance of dynamic capabilities in gaining competitive advantage and improving the organisational performance, recent studies have focused on its human-behavioural micro-foundations as a basis for improving dynamic capabilities at organisations macro level. This article reviewed the literature in the field of behavioural and human resource foundations of dynamic capabilities using a systematic literature review method and evaluated the quality of articles with CASP method. After a systematic review of 41 final articles, 15 themes were identified for the behavioural foundations of dynamic capabilities. The sensing dimension includes personal and interpersonal indicators, in seizing dimension, indicators of communication, conflict management, organisational climate, etc. The reconfiguring dimension involved the indicators of knowledge management, leadership, talent management, capacity building, and diversity of employees.